Analisis TPAK Perempuan di Wilayah Riau Pesisir - Murialti, Neng; Hadi, M. Fikry; Algusri, Jeki; Bakaruddin, Bakaruddin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This research analyzes the factors that influence women's TPAK in the Riau Coastal region. The data analysis technique used in this research is panel data regression. Panel data combines cross section data covering six city districts in the Riau Coastal region with the 2018-2022 time series. The research results show that the model chosen to answer the objectives of this research is the Common Effect Model. The partial test results of women's productive age, wage level, unemployment rate, and women taking care of the household have a significant effect on women's TPAK in districts and cities in the Riau Coastal region, while the variable level of women's education is negative and not as important as women's TPAK in districts/cities. is in the Riau Coastal region. Meanwhile, by using a simultaneous test, all the variables in this study have a significant effect on Women's TPAK in the Riau Coastal Region.